IoT Based Plant Watering Irrigation and Monitoring System - Smail, Mohammad Iqhram; ZAINAL, MOHD SHAMIAN (Progress in Engineering Application and Technology, 2025)
Before the advent of monitoring systems, farmers would spend hours daily tending to seedlings, which required meticulous care. This project report introduces an Internet of Things (IoT)-based plant irrigation and monitoring system designed to automate and streamline the watering process for various plant species. The system’s primary goal is to maintain optimal soil moisture levels, which improves plant health while reducing water waste. The system continuously monitors the ambient parameters surrounding the plants using sensors for temperature, humidity, and soil moisture. Sensor data is sent to a central microcontroller when soil moisture drops below a preset threshold. After processing the input, the microcontroller turns on the irrigation system. Wireless connection protocols and cloud-based data storage enable this automation, giving customers real-time control and system monitoring via an easy-to-use software program. In order to create well-informed irrigation decisions, an intelligent algorithm analyses sensor inputs while accounting for weather, soil characteristics, and plant kind. The system was put through rigorous field testing, software algorithm refining, and hardware design validation during the implementation phase. The test findings showed notable increases in plant health and water-use efficiency when compared to conventional irrigation techniques. By using an ESP32 board module, the system makes it simple for users to monitor and manage the process via Arduino IoT Cloud, increasing convenience. The goal of this all-encompassing strategy is to provide a practical, effective answer for contemporary farming methods